World Heritage Conservation in the Pacific The Case of Solomon Islands - Price, Stephanie Clair (Palgrave Series in Asia and Pacific Studies, 2018)
This book explores the opportunities and challenges associated with the legal protection of World Heritage sites in the Pacific Islands. It argues that the small Pacific representation on the World Heritage List is in part due to a lack of strong legal frameworks for heritage conservation, putting such sites under threat. Providing a comprehensive analysis of the nomination, listing and protection of the Solomon Island World Heritage Site, it examines the implementation of the World Heritage Convention in the Pacific context. It explores how the international community's broadening interpretation of the notion of 'outstanding universal value' has increased the potential for Pacific heritage to be classified as 'World Heritage'. This book also analyses the protection regime established by the Convention, and the World Heritage Committee's approach to heritage conservation, identifying challenges associated with the protection of Pacific Island heritage. .